The determinants of public investment in Ethiopia: An ARDL approach - Solomon Tilahun (Cogent Economics & Finance, 2021)
Public investment has shown increasing trends both in nominal and as a share of GDP over years in Ethiopia. These upsurges in public investment are believed to be due to factors that have visible impact on the fiscal posture of the country. To investigate the validity of Wagner's law in Ethiopia; this study sets determinants of public investment in Ethiopia as a general objective. Specifically, the study sought to examine the main influencing factors on level of public investment in Ethiopia along three sets of explanatory variables. In order to meet the aforementioned objective, the study employed an autoregressive distributed lag (ARDL) approach over the period 1985-2019. Results from the bound tests show that there is a long-run relationship between the variables. The real per capita GDP is found to be positively and significantly impact on level of public investment which shows that there an evidence in favour of Wagner's law,i.e. public spending has a high income elasticity of demand. This study also found that there is a positive relationship between public investment and private investment which shows that two are moving in tandem. Again, the study also found that foreign aid has positive impact on public investment implying that additional foreign aid leads to larger spending of the government on capital. Moreover, the study found that the degree of urbanization suggests that levels of public spending are higher in the urban sector than rural economies. These findings give strong policy implication to the policy makers because an increase in public investments in may then help spur economic growth.
Keywords: 330; ARDL; Economic Growth; Ethiopia; public investment; Wagner's law